Exploration of the effect of ultrasound treatment on starch-theanine-EGCG complexes based on multi-scale structure and prediction of the interaction by density functional theory calculations - Zongwei Hao; Huijun Sun; Xinran Liu; Yixuan Xu; Jiameng Wang; Hui Xu; Zhongyun Zhao; Zongjun Wu; Mingming Zheng; Yibin Zhou; Zhenyu Yu (Food Chemistry: X)
Ultrasonication (US) is an emerging green modification technique in food science, yet its impact on starch-tea active ingredient interactions and digestibility remains underexplored. This study investigated the effects of US on maize starch (MS) complexed with epigallocatechin gallate (EGCG) and L-theanine (THE). US induced agglomeration and adhesion, increasing viscosity (p < 0.05) and enhancing the multi-scale structural order. The relative crystallinity increased to 30.82 %, improving thermal stability, while rapidly digestible starch decreased by 16.57 %, and resistant starch increased to 34.29 %. Pearson analysis indicated a strong correlation between starch digestibility and structural changes. Density functional theory calculations revealed hydrogen bonding and van der Waals forces as dominant interactions in MS-THE/EGCG complexes. These findings provide a theoretical basis for optimizing US conditions and enhancing the utilization of tea-derived bioactives in starch-based foods.